Prolonged video capsule endoscopy examination durations can improve capsule endoscopy completeness - Kai-Liang Lin; Kuan-Yi Sung; Yong-Cheng Ye; Yen-Po Wang; Tien-En Chang; Pei-Shan Wu; Jiing-Chyuan Luo; Ming-Chih Hou; Ching-Liang Lu (BMC Gastroenterology, 2024)
Abstract Background Capsule endoscopy (CE) is useful for managing patients with suspected small bowel diseases. However, the effect of prolonged CE examination time on CE performance is unknown. Aim To evaluate the completeness and diagnostic yield of prolonged CE imaging in patients with suspected small bowel bleeding. Methods We reviewed consecutive records of adult CE examinations via an overnight protocol from Jan 2016 to Dec 2020 at a tertiary center in Taiwan. We subcategorized the CE records by recording length into within 8 h, within 12 h and throughout the whole procedure and compared the completion rate and diagnostic yield between the groups. Cochran’s Q test was used for statistical analysis. Results A total of 88 patients were enrolled with 78.4% inpatients (median age 72 years). The small bowel evaluation completion rate was 93.2%, which was significantly greater than the 79.5% rate within 12 h (p = 0.025) and the 58% rate within 8 h (p < 0.001). The diagnostic yield was 83% in the whole-course overnight study, which was significantly greater than the 71.6% diagnostic yield within 8 h (p < 0.001) and similar to the 81.8% diagnostic yield within 12 h. Conclusion Prolonged overnight CE examination can improve the completion rate and diagnostic yield and should be considered for routine clinical practice.